Behavior change following diagnosis with acute/early HIV infection-a move to serosorting with other HIV-infected individuals. The NIMH Multisite Acute HIV Infection Study: III. - Steward, Wayne T; Remien, Robert H; Higgins, Jenny A; Dubrow, Robert; Pinkerton, Steven D; Sikkema, Kathleen J; Truong, Hong-Ha M; Johnson, Mallory O; Hirsch, Jennifer; Brooks, Ronald A; Morin, Stephen F (AIDS and behavior, 2009)
Risk reductions behaviors are especially important during acute/early HIV infection, a period of high transmission risk. We examined how sexual behaviors changed following diagnosis of acute/early HIV infection. Twenty-eight individuals completed structured surveys and in-depth interviews shortly after learning of their infection and 2 months later. Quantitative analyses revealed significant changes after diagnosis, including reductions in total partners and decreases in the proportion of unprotected sex acts occurring with uninfected partners (serosorting). Qualitative findings indicated that these changes were motivated by concerns about infecting others. However, participants were less successful at increasing the frequency with which they used condoms. These results suggest that the initial diagnosis with HIV may constitute an important component of interventions to promote risk reduction during the acute/early stages of the disease.
Keywords: Adult; AIDS Serodiagnosis; Condoms; Evaluation Studies as Topic; Female; Health Behavior; HIV; HIV Infections; Humans; Male; Risk Factors; Risk Reduction Behavior; United States; Unsafe Sex; Young Adult